TINJAUAN HUKUM ISLAM TERHADAP TRANSAKSI JUAL BELI BUKET UANG PERSPEKTIF SAYYID ABU BAKRI SYATHA DALAM KITAB I’ANATU ATH-THALIBIN - Wahab, Fatkhul; Muhammad Zainur Roziqin (LP3M IAI Al-Qolam, 2023)
In this millennial era, many buying and selling transactions were found that did not exist at the time of the Prophet Muhammad. One of them is buying and selling bouquets in the form of money. There is no discussion of this transaction in the classics. However, this problem is interesting to study in the perspective of Sayyid Abu Bakar Syāthā in his book I’ānah al-Thālibīn. This is descriptive qualitative research using the Content Analysis method. Data sources include primary data sources, namely the perspective of Sayyid Abū Bakr Syāthā in his book I’ānah al-Thālibīn, and secondary data sources, namely Syafi'iyyah fiqh books, journals, and literature relevant to the material being studied. The data collection technique is to examine primary sources and secondary sources. The results of the study show that there are 3 important points in buying and selling a bouquet of money, namely: (1) buying and selling a bouquet of money is permissible if the pillars and conditions are met. (2) the buying and selling of bundles of money does not include usury so that there is no addition to the transaction (3) money is not included in the category of assets.